Antioxidant Capacity and Radical Scavenging Effect of Polyphenol Rich Mallotus philippenensis Fruit Extract on Human Erythrocytes: An In Vitro Study - Mayank Gangwar; Manish Kumar Gautam; Amit Kumar Sharma; Yamini B. Tripathi; R. K. Goel; Gopal Nath (The Scientific World Journal)
Mallotus philippinensis is an important source of molecules with strong antioxidant activity widely used medicinal plant. Previous studies have highlighted their anticestodal, antibacterial, wound healing activities, and so forth. So, present investigation was designed to evaluate the total antioxidant activity and radical scavenging effect of 50% ethanol fruit glandular hair extract (MPE) and its role on Human Erythrocytes. MPE was tested for phytochemical test followed by its HPLC analysis. Standard antioxidant assays like DPPH, ABTS, hydroxyl, superoxide radical, nitric oxide, and lipid peroxidation assay were determined along with total phenolic and flavonoids content. Results showed that MPE contains the presence of various phytochemicals, with high total phenolic and flavonoid content. HPLC analysis showed the presence of rottlerin, a polyphenolic compound in a very rich quantity. MPE exhibits significant strong scavenging activity on DPPH and ABTS assay. Reducing power showed dose dependent increase in concentration absorption compared to standard, Quercetin. Superoxide, hydroxyl radical, lipid peroxidation, nitric oxide assay showed a comparable scavenging activity compared to its standard. Our finding further provides evidence that Mallotus fruit extract is a potential natural source of antioxidants which have a protective role on human Erythrocytes exhibiting minimum hemolytic activity and this justified its uses in folklore medicines.